PENGARUH GAYA KEPEMIMPINAN DAN KECERDASAN EMOSIONAL TERHADAP KINERJA PERSONEL KEPOLISIAN RESORT (POLRES) SAMPANG YANG DIMEDIASI OLEH DISIPLIN KERJA - Dwi Abdillah; Chamariyah Chamariyah; Subijanto Subijanto (Universitas 45 Surabaya, 2022)
The aims of this study are: 1) to test and analyze whether leadership style has a significant effect on performance; 2) to test and analyze whether leadership style has a significant effect on the work discipline of the Sampang Police Resort (Polres); 3) to test and analyze whether emotional intelligence has a significant effect on personnel work discipline; 4) To test and analyze whether emotional intelligence has a significant effect on personnel performance; 5) to test and analyze whether work discipline has a significant effect on personnel work discipline; 6) to test and analyze whether leadership style has a significant effect on personnel performance mediated by personnel work discipline; 7) to test and analyze whether emotional intelligence has a significant effect on personnel performance mediated by work discipline. The results showed that: 1) Leadership style had a positive and significant effect on personnel performance. This is evidenced by the original sample value of 0.351 and the p-values of 0.000; 2) leadership style has a positive and significant effect on work discipline. This is evidenced by the original sample value of 0.491 and the p-values of 0.000; 3) emotional intelligence has a positive and significant effect on work discipline. This is evidenced by the original sample value of 0.256 and p-values of 0.000; 4) Emotional intelligence has no significant positive effect on performance. This is evidenced by the original sample value of 0.148 and the p-values of 0.000; 5) work discipline has a positive and significant effect on personnel performance. This is evidenced by the original sample value of 0.345 and p-values of 0.004; 6) leadership style has no significant positive effect on performance mediated by work discipline. This is evidenced by the original sample value of 0.169 and the p-values of 0.000; 7) emotional intelligence has no significant positive effect on personnel performance mediated by work discipline. This is evidenced by the original sample value of 0.088 and the p-values of 0.000.